Creating Sliding Erasure by Using Plastic Bottles to Minimize Trash in School Environment in Bestlink College of the Philippines (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
The students of Bestlink College of the Philippines throw plastic bottles in trash bins; thus, instead of considering plastic bottles as waste, we can reuse them by recycling. This topic is serious because recycling plastic bottles can lead to more waste in the school and help the utility staff in segregating trash. The objectives of our research were to help the school and help the students become more eco-friendly. The overall purpose of this study was to lessen the problems of throwing plastic bottles. The researchers surveyed 50 grade 12 Accountancy, Business, and Management Strandstudents to gather information. The recycled sliding erasure helped the students and teachers in continuing the lessons and made the school more unique in terms of new quality erasure. This study can provide several advantages to Bestlink College of the Philippines, especially to students and teachers who are using the classrooms. This recycled sliding erasure will be the first thing that will be launched in the Philippines.
Keywords: sliding erasure